2022
DOI: 10.7860/jcdr/2022/55604.16186
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Space-time Clustering of Diarrhoeal Cases among Under-Five Children in Karkala, Karnataka: A Geospatial Analysis

Abstract: Introduction: Globally, India tops by contributing the maximum number of diarrhoeal fatality. Forecasting the path and spread of diarrhoeal disease is critical due to its multifactorial cause, which needs robust spatial analysis and experiential investigations of communicable disease. Aim: To investigate purely spatial, purely temporal, and spacetime clusters of diarrhoea among under-five children using a Geographic Information System (GIS) in Karkala taluk of the Udupi district of Karnataka, India. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…secondary clusters of diarrheal cases were identified covering 18 villages. Purely temporal cluster were also identified during summer season(20). Since such spatial distributions have been correlated to factors such as socio-demographic factors, environmental factors climate change(21), a further in-depth study investigating such under-lying factors could be useful in associating to hotspots identified in this study.…”
mentioning
confidence: 72%
“…secondary clusters of diarrheal cases were identified covering 18 villages. Purely temporal cluster were also identified during summer season(20). Since such spatial distributions have been correlated to factors such as socio-demographic factors, environmental factors climate change(21), a further in-depth study investigating such under-lying factors could be useful in associating to hotspots identified in this study.…”
mentioning
confidence: 72%
“…The cluster approach is arelatively new approach to the study of the spatial distribution of communicable diseases that has been used in different parts of the world, e.g., work on tuberculosis (TB) has been done in Mexico by Bastida et al (2012), in Nigeria by James (2016), in Zimbabwe by Chirenda et al (2020) and in Bandung, Indonesia by Puspita et al (2021). Similar work regarding malaria has been carried out in Ghana by Magna et al (2019) and the presence of clustered areas of people affected by diarrhoeal disease in Karkala Karnataka, India was recently reported by Dmello et al (2022). At the same time, Almasi et al (2022) investigated the global occurrence from 2000 to 2017 of clustered areas of diarrhoea-related mortality (DRM) in children under five and found that Asian and African countries had the highest incidence of DRM in this period.…”
Section: Introductionmentioning
confidence: 93%